Pengaruh Pengendalian Internal dan Sistem Informasi Akuntansi Terhadap Pencegahan Fraud pada Dinas Sosial Kabupaten Luwu - Nur Vadillah; Andika Rusli; Indah Pratiwi (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
This research aims to find out and identify the extent of the influence of internal control and accounting information systems on fraud prevention in the Luwu Regency Social Service. The research method used is quantitative with a survey method by distributing questionnaires. The population in this research is all employees in the Social Service. This sampling used purposive sampling. The number of respondents  was 51. The data used in this research is primary data which was conducted using a survey method with a questionnaire. The data analysis method in this research uses multiple linear regression with application tools, namely SPSS (Statistical Product and Service Solutions). Based on the research results, it can be concluded that internal control variables and accounting information systems have a positive and significant effect on preventing fraud at the Luwu Regency Social Service.